Profit Maximization for Cloud Broker in Cloud Computing - Namose, MS; Shinde, AN; Patil, CR; Rodage, VR; Awalekar, ND (International Journal of Computer Sciences and Engineering, 2021)
oday’s world cloud computing becoming so popular because of an effective and efficient way to provide computing resources and services to customers on demand. Cloud computing being an information technology paradigm enables access to shared pools of configurable system resources and higher-level services often over the Internet. The objective of providers is to maximize profits by their price schemes, while the main purpose of clients is to have quality of services for a reasonable price. Thus the vital aim is to maximize the profit for service providers get quality of service at best price for the client. Because of cloud computing development, choosing cloud services can be complicated time- consuming for customers. To facilitate cloud service delivery, the authors propose a cloud service broker who provides automated selection of suitable cloud services, assure the best performance, reliability, cost efficiency.